2021
DOI: 10.1038/s41598-021-95034-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of Pseudomonas aeruginosa strains isolated from cystic fibrosis patients

Abstract: Pseudomonas aeruginosa is a severe bacterial pathogen. Due to the genetic flexibility among strains, chronic airways infection can lead to mortality among cystic fibrosis (CF) patients. It is essential to develop patient-specific therapy which will rely on phenotypic and genomic diversity. The primary objective of this study was to assess the genomic variability of P. aeruginosa strains, using two different molecular techniques for tracking the epidemiological transmissions. This study applied a multiple-locus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…A study by Jarych et al, irrespective of geographical distance and sample origin (different clinical samples vs. CF patients), supports our findings, suggesting that MLVA is a robust genotyping method applicable for systematic surveys of P. aeruginosa isolates in patients. The study demonstrates the method's effectiveness in discriminating isolates (23).…”
Section: Discussionmentioning
confidence: 82%
“…A study by Jarych et al, irrespective of geographical distance and sample origin (different clinical samples vs. CF patients), supports our findings, suggesting that MLVA is a robust genotyping method applicable for systematic surveys of P. aeruginosa isolates in patients. The study demonstrates the method's effectiveness in discriminating isolates (23).…”
Section: Discussionmentioning
confidence: 82%
“…The genomes of the underlying P. aeruginosa show little variability in the early stage of a chronic lung infection, but with the duration of the chronic course, single nucleotide mutations and genetic inversions in accessory and housekeeping genes result in diversification. On the other hand, previous studies showed that CF patients can be simultaneously colonized by several different strains that might be residents of the pulmonary tract microbiome prior to an exacerbation [62,63]. All these findings emphasize that antimicrobial resistance testing based solely on a single isolate may lead to ineffective treatment against other coexisting subspecies within the cystic fibrosis (CF) lung.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the well-documented variability in P. aeruginosa strains that occupy the CF lung. This variability underscores the complexity of managing infections in CF patients, as the differences in phage susceptibility and antibiotic resistance can significantly impact treatment efficacy and outcomes (26).…”
Section: Clonality Of the Isolatesmentioning
confidence: 99%